"White Practices" in Adult Education Settings: An Exploration - Sue Shore (Adult Education Research Conference, 2000)
This paper draws together literature from the newly emerging areas of studies about Whiteness, and postcolonial theory to provide an alternative analysis of the Inquiry processes into adult community education undertaken in Australia over the last decade.